Proposta de implantação da Norma Regulamentadora Nº10 - segurança em instalações e serviços em eletricidade para empresas de construção elétrica em Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
There are numerous accidents at work in electrical construction, which annually cause severe sequelae or even lead to the death of many workers in the country. For this reason, the Ministry of Labor and Employment (MTE) has regulated the Regulatory Norm NR nº10, Safety in Facilities and Services in Electricity, which establishes the minimum requirements and conditions for control measures and preventive systems to guarantee safety and Health of workers who, directly or indirectly, interact in electrical installations and service with electricity.The present work has objected to carry out na implementation diagnosis to NR nº 10,through a check listo f the requirements of the standard, in three companies conducting electrical construction services in Manaus.Base on this diagnosis it was possible to identify which the requirements of NR nº10 attended, the non-covered, partially responsible, in order to subsidy, for decision making necessary.The methodology used in this analysis is descriptive, case study, qualitative, bibliographical research and documental analysis.It concludes that the implementation of NR nº10 is beneficial, that their cost of implantation and the resistance covered by some workers in the sector can be overcomeed by the benefits it will generate.The implementation of this standard in the company will encourage a safer environment to achieve the activities, bringing it out as a result of a lower number of work accidents and traumatic diseases for workers, which will certainly create a larger sense of safety, by making them they can produce with greater celerity.For government agencies the greatest benefit will be the reduction of expenses with the removal of workers from their activities.
Keywords: Norma Regulamentadora nº 10; Segurança no trabalho; Acidentes de Trabalho; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO